Advanced Control Technology of Photovoltaic Power Generation Systems For Safety, Efficiency, Reliability, and Adaptability - Zhang, Chenghui; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
The photovoltaic (PV) inverter serves as the interface between the PV panels and the power grid and realizes the power conversion, which is the core equipment of the PV power generation system. With the development of PV industry, the requirements of functions or performances for PV inverters are also gradually proposed in practical applications, which consist of safety, generation efficiency, transmitted power quality, robustness to multiple disturbances, grid-friendly, continuity of power supply, and system reliability. To satisfy these requirements, this book puts forward a series of software-based advanced control technologies for PV inverters. Through these control technologies, the PV power generation system has gradually become a system with high safety, high reliability, high efficiency, and strong adaptability, which serves as a core support in modern power system. To facilitate the understanding, the operating principle, model derivation, control schemes, and comprehensive verification results of the PV inverters are presented step by step in this book, which can serve as a guide for electrical engineers and researchers involved in the development of PV power generation. This is an open access book.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Photovoltaic power generation; Control engineering; Renewable energy sources; Electronic circuits; Photovoltaics; Control and Systems Theory; Renewable Energy; Electronic Circuits and Systems